Disentangling rural smartness in European policies: a critical overview of the Smart Village concept - Valentina E. Albanese; Teresa Graziano (AIMS Geosciences)
In recent years, several policies have increasingly considered smart technologies as a potential solution to overcome territorial marginality in rural areas, where digitalization and smart innovation could help local communities address challenges such as depopulation and socio-economic deprivation. At the European scale, the Smart Village Action was launched in 2017 to address the so-called 'circle of decline', showing to what extent rural smartness has been recently gaining momentum in transnational cohesion policies. This work aims to critically explore the Smart Village paradigm as a recently-emerged policy framework in rural, cohesion and/or recovery policies, investigating if and how it is variously (re)interpreted in policies and operationally applied in projects. From a methodological point of view, a qualitative policy document analysis (QPDA) and software-based content analysis were carried out on UE official documents, offering new theoretical insights and operational recommendations for understanding the concept of smartness beyond urban-centered perspectives.